Winter grave - Tursten, Helene, 1954- (Tursten, Helene, 1954- Embla Nyström investigations, 2019)
When a little girl disappears a few weeks before Christmas, suspicion falls on the last person she was seen with: the mentally disabled teenage boy who gave her a ride home after school. Complicating the matter is the fact that detectives can hardly get a word out of him. When a second child disappears and a police officer is found dead, tensions in the small town of Strömstad reach an all-time high. Meanwhile, 28-year-old Detective Inspector Embla Nyström has just returned to work and is still recovering from her recent brush with a killer, which left her unable to get back in the ring to defend her title of Nordic light welterweight champion. As she hunts for the missing children, Embla can<U+2019>t help but think of the case that has been haunting her for years: the disappearance of her childhood best friend. Could the incidents be linked? With the passing of each dark winter day, the odds of finding the children alive shrink, and desperation mounts. Their parents want answers and will stop at nothing to get them.